Burr-Assisted Anterior Lamellar Keratoplasty (DALK) in Patients with Corneal Stromal Scarring: A Case Series - Kymionis, George D. (Ophthalmol Ther, 2020)
PURPOSE: To describe a modified technique of deep anterior lamellar keratoplasty (DALK) assisted by diamond ophthalmic burr (DOB) in two patients with corneal stromal scarring. METHODS: Two patients with corneal stromal scarring underwent a modified DALK technique with corneal stromal polishing assisted by a DOB until the level of the Descemet membrane. RESULTS: There were no intra- or postoperative complications. Six months postoperatively, the corneal graft was clear, while corrected distance visual acuity improved in both cases. CONCLUSIONS: Burr-assisted DALK seems to represent an alternative surgical technique in patients with corneal stromal scarring. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40123-020-00248-8) contains supplementary material, which is available to authorized users.